Cashless payments influence impulse buying behaviour / Dr. Syahida Abd Aziz and Dr. Roziyana Jafri - Abd Aziz, Syahida; Jafri, Roziyana (Universiti Teknologi MARA, Kedah, 2023)
Consumers today are more likely to purchase a product on a whim, regardless of whether they are shopping online or in-store. Consumers become increasingly prone to making rash decisions as time passes. Numerous individuals engage in more casual or compulsive shopping, particularly via online channels. As technologies have advanced, debit and credit cards, e-wallets with quick response (QR) code options, contactless cards such as SamsungPay, ApplePay, MAE, and the Buy-Now-Pay-Later (BNPL) feature, as well as many others have become more prevalent, thereby accelerating the process of making a purchase. With mobile wallets gaining the most traction among first-time users (33%) followed by online cards (30%) and QR code payments (26%), cashless payments are on the rise (Visa, 2022). As a result of this significant shift in consumer behaviour and the widespread adoption of digital payment methods, Malaysia is gradually becoming a cashless society.